Are the kids alright? The early careers of education leavers since the COVID-19 pandemic - Sam Ray-Chaudhuri; Xiaowei Xu (Institute for Fiscal Studies (IFS), 2023)
In this report, we present the first evidence on how the cohorts of young people who entered the labour market during the pandemic have fared up to now. In Section 2, we discuss why we might expect the pandemic to lead to scarring effects, documenting how labour market outcomes evolved over the pandemic and comparing trends with the 2008 recession to demonstrate the magnitude of the COVID-19 shock for young people. In Section 3, we focus on the cohorts of young people who entered the labour market during the COVID-19 years, or just before, comparing their employment rates and multiple measures of job quality with those of earlier cohorts to assess the extent to which they are likely to experience long-term scarring as result of the pandemic. In Section 4, we discuss the prospects for future cohorts due to enter the labour market in the coming years. We conclude in Section 5.
Keywords: 330; Employment and income; Labour markets supply and workforce; Labour markets; Employment; COVID-19; Human capital